PEMANFAATAN MEDIA PEMBELAJARAN PUZZLE TERHADAP PENGETAHUAN KEANEKARAGAMAN NUSANTARA SISWA KELAS KELAS 4 SD LABORATORIUM UM - Kustiawan, Usep; Cholila, Indhira; Rahman, Aulia; Zakaria, Muhammad; Rahmalia, Acnes; Sogen, Archangela; Wildayati, Salma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Field conditions show that learning in grade IV requires concrete, latest and innovative learning media. This study aims to test the validity, attractiveness and effectiveness of the Nusantara Puzzle which was developed to help students in learning. This study uses the RnD (Research and Development) method with the ADDIE (Analyze, Design, Development, Implementation, Evaluation) model. This study was conducted at SD Laboratorium UM with research subjects being grade IV-Bilingual students. Material validation obtained a percentage result of 97.5% stated as very valid. Media validation obtained a percentage result of 97.91% stated as very valid. The attractiveness test from users (teachers) obtained a percentage result of 94.23% stated as interesting. To test the effectiveness of the product, researchers used pre-experimental research by conducting a Sign test with the results of increased learning of 22 students.